2018
DOI: 10.12659/msm.907400
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Preoperative Low-Density Lipoprotein Cholesterol and Periprocedural Myocardial Injury in Patients Following Elective Percutaneous Coronary Intervention in Southern China

Abstract: BackgroundPeriprocedural myocardial injury (PMI) is known to be a predictor of postprocedural cardiovascular morbidity and mortality following a percutaneous coronary intervention (PCI). However, the correlation between low-density lipoprotein cholesterol and periprocedural myocardial injury in patients following elective PCI in southern China remains unclear. Therefore, we aimed to investigate the association of preoperative low-density lipoprotein cholesterol (LDL-C) levels with PMI in patients following ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…We also observed that the treatment for risk factors in the young CHD patients before admission were also low, with only 16.9%, 8.1%, 13.7%, and 10.9% of patients treated with anti-hypertensive, antidiabetic, anti-platelet medications, and statins, respectively. These data strongly support the notion that risk factor treatment is essential to prevent CHD [24]. Interestingly and importantly, we found that the reason most of young CHD patients underwent coronary artery stenting was not due to myocardial infarction.…”
Section: Discussionsupporting
confidence: 88%
“…We also observed that the treatment for risk factors in the young CHD patients before admission were also low, with only 16.9%, 8.1%, 13.7%, and 10.9% of patients treated with anti-hypertensive, antidiabetic, anti-platelet medications, and statins, respectively. These data strongly support the notion that risk factor treatment is essential to prevent CHD [24]. Interestingly and importantly, we found that the reason most of young CHD patients underwent coronary artery stenting was not due to myocardial infarction.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous evidences have revealed that LDL-C serum concentrations correlate with very high cardiovascular risk and stringent LDL-C lowering with statins therapy is recommended for the secondary prevention of recurrent cardiovascular events and survival improvement after PCI by the current international guidelines [16, 17]. Another research of ours found that PCI patients with lower preprocedural LDL-C were less risky to periprocedural myocardial injury in southern China [18]. Data from patients treated with statins show considerable gains by approximately 22% per 1.0 mmol/L LDL-C reduction [19].…”
Section: Introductionmentioning
confidence: 91%
“… 20 , 23 In addition, the independent predictive value of total stent length was demonstrated, which also provided evidence with interventional cardiologists when making procedural plans to prevent UA patients from adverse myocardial injury and neurosis. Other studies have found that postoperative LDL-C is associated with perioperative myocardial infarction and long-term prognosis, 11 , 20 , 23 but in this study, the OR value was statistically analyzed after the classification of LDL-C. In addition, the relationship between total stent length and perioperative myocardial infarction was found in this study, which has hardly been reported in other studies.…”
Section: Discussionmentioning
confidence: 78%
“…Patients with UA were characterized as having ischemic symptoms at rest or minimal exertional without myocardial infarction. 20 …”
Section: Methodsmentioning
confidence: 99%